PARENTING AND CHILDREN'S EMOTIONAL DEVELOPMENT - Oktaviani, Maya; Dwijulianto, Aditya; Istiqoma, Aisya Putri; Saefullah, Deza Rajulirahma; Sagita, Fitri; Nabiel, Maryam; Devi, Shavira Karunia (IJBLE Scientific Publications Community Inc., 2023)
Every child is born with His nature, and children are entitled to good education and upbringing to build their character. Parents have a crucial role in forming a child's character. Parents become role models for their children, so they must choose a good parenting pattern. In addition to parenting provided by parents, the environment is also one of the influences in forming children's character. This study aims to determine the influence of parents' parenting on children's emotional development. The sample of this study consisted of 15 parents and 15 children aged 12-20 years, using a quantitative survey method that focuses on the views between parents and children. This study indicates that there is indeed an influence caused by choice of parenting patterns on children's emotional development.